(3eNJUQ ef eJHdL GdCfhGQ heJGQL GdfhGQs - (3CHhGdecGQe mCYO Hf egPH Hf ejfG Hf RcQjG, GHf eeGJjs ((3CMeO Hf YHOGdhGSY GdbQTj s)
(3ChdgG (B:s
(3gPG eNJUQ ef eJHdL GdCfhGQ aj GdecGJHGJ Edi Gdedhc hGdhRQGA hGdYdeGA hZjQge s
(3BNQgG (B:s
(3COGQ aj Cab GdSjGOI adcgG hNGWQce UGdM GdOYGA eY GdeSdejf Je GdeNJUQ GdeHGQc s
(3Vef eLehY , JQJjHgG (B: (3ef U (B31 - (3U(B57 (3Cs
(3eeG LeYg GHf eeGJj ef bhd GdbGVjs
(3HBNQ cd UaMI JYbjHI s
(3haj NJGegG bQGAI hJMUjd eDQN aj SfI (B1207(3g``s
(3HBNQgG ecGJHGJ eNJdaI aj CHhGH YTQIs
(3JHUQI GdYfhGf (B:s
(3LeYs
Keywords: (3GdCOHs